ANALISIS DESAIN EMBUNG SEBAGAI PENGATUR SUPLAI AIR IRIGASI DENGAN MENGGUNAKAN METODE WATER BALANCE (STUDI KASUS: EMBUNG KOLAK DESA TEMPUREJO KECAMATAN WATES KABUPATEN KEDIRI) - Vanesa Indriani; nurjanah nurjanah (Universitas Islam Balitar Blitar, 2021)
Embung compote is a water structure that functions to distribute and ensure the availability of water supply for crops or livestock in the dry and rainy season. Located in Tempurejo Village, Wates District, Kediri Regency. Embung is a micro-sized water reservoir (reservoir) around agricultural land that is built to accommodate the amount of rainwater during the rainy season and become a supply in the dry season. The current condition in the reservoir source compote is experiencing a problem of decreasing water resources and part of the reservoir building is leaking. The initial step of this research is hydrological analysis to determine monthly rainfall, effective rainfall R80, effective rainfall 10 days. The results of the analysis are then used to calculate water requirements using the Water Balance method and design planning of the compote reservoir. Water Balance / Water Balance is a comparison between the available water debit and the water required for irrigation purposes. Based on the results of the analysis and design planning of the embung, the dimensions of the embung are 2.3 m high, round lighthouse type, 1 flushing door with a size (2.14 mx 1 m), a volume of water reservoir is 1.086.84 m3, foundation depth is 0.8 m , the volume of the foundation is 0.217 m3 which can withstand a load of 3.255 tons.